New solutions of the fractional Boussinesq-like equations by means of conformable derivatives - Korpinar, Z.; Tchier, F.; İnç, Mustafa; Ragoub, L.; Bayram, M. (Elsevier, 2019)
In this paper, the process of the extended direct algebraic method (EDAM) is used to solve two fractional Boussinesq-like equations by means of conformable derivatives. Firstly, these fractional equations are changed into the ordinary differential equations by using the traveling wave transformation. Then new solutions are obtained by using EDAM. This dynamical model plays a key role in engineering and physics. The constructed solitons solution help researchers in understanding the physical phenomenon of this equation. The standard linear stability analysis is utilized and the stability of the model is investigated which substantiate that all results are stable and exact. Graphically, the movements of some solutions are depicted at appropriate values of parameters. The achieved results show simplicity, reliability, and power of the current schemes.
Keywords: Boussinesq-like equations; Conformable derivative; The extended direct algebraic method